Agencies, assemblages and affective traces - Matylda Jonas-Kowalik (Nordisk Judaistik)
Review of Victoria Van Orden Martínez, Afterlives: Jewish and NonJewish Polish Survivors of Nazi Persecution in Sweden Documenting Nazi Atrocities, 1945–1946. Ph.D. thesis, Linköping University, 2023. 278 pp.